Impact of Newly Planned Detectors on the Standard Model Analysis of pp → W+Z at the HL-LHC - ALYASIRI, Muhanad; Gaber FAISEL (International Journal of Computational and Experimental Science and Engineering, 2025)
The High-Luminosity Large Hadron Collider (HL-LHC) promises unprecedented sensitivity to Standard Model (SM) processes and new physics scenarios. This study focuses on the production of pp → W+Z, with subsequent decays W+ → ℓ+ νe and Z → ℓ+ ℓ−. We explore the impact of planned detector upgrades on precision measurements and sensitivity to Beyond Standard Model (BSM) phenomena. Using insights from simulations, this paper highlights the role of advanced detectors in improving reconstruction, reducing uncertainties, and extending the discovery reach in vector boson interactions.